2023
DOI: 10.3390/cancers15020339
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Pancreatic Metastases of Renal Cell Carcinoma—Clinical Particularities and Seed and Soil Hypothesis

Abstract: A meta-analysis of 1470 isolated pancreatic metastases of renal cell carcinoma revealed, that, in addition to the unusual exclusive occurrence of pancreatic metastases and the favourable treatment results, the isPMRCC is characterised by further peculiarities of the clinical course: The lack of prognostic significance of volume and growth rate dependent risk factors and the independence of treatment results from standard or local resections. As an explanation for all these peculiarities, according to today’s k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 268 publications
(215 reference statements)
0
5
0
Order By: Relevance
“…The most common intrapancreatic RCC metastases are those of the clear cell subtype [45]. The striking differences between the relative frequency of RCC metastases between surgical and autopsy cohorts may be explained by their rather good prognosis and often solitary occurrence, which makes these patients more likely to qualify for pancreatic resection than those with pancreatic metastases from other primary tumors [22,39,43,46,47].…”
Section: Disease Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…The most common intrapancreatic RCC metastases are those of the clear cell subtype [45]. The striking differences between the relative frequency of RCC metastases between surgical and autopsy cohorts may be explained by their rather good prognosis and often solitary occurrence, which makes these patients more likely to qualify for pancreatic resection than those with pancreatic metastases from other primary tumors [22,39,43,46,47].…”
Section: Disease Frequencymentioning
confidence: 99%
“…Sellner et al calculated cumulative 5-year and 10-year survival rates of 75.7% and 47.3%, respectively, from 415 casuistically reported postoperative observations in RCC pancreatic metastases [42]. According to the meta-analyses of Adler et al, Huang et al, and Sellner et al, none of the following factors significantly influence treatment outcomes: singular or multiple localization of RCC metastases; synchronous or a metachronous occurrence; the interval to nephrectomy; size of metastases [33,39,41,43,46]. Nevertheless, Rodger et al, in their most current systematic review of 35 cohort studies, reported that a metachronous presentation and a longer disease free interval before the presentation of intrapancreatic metastases were significantly associated with better survival outcomes [105].…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, patients with metastases to the liver, bones, and brain tend to have the worst prognosis. However, patients with endocrine metastases, such as pancreatic metastases, even though rare, exhibit a significantly prolonged disease course and a better outcome [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Side-effects of targeted agents may include, but are not limited to, diarrhoea, skin effects, and lethargy, whereas more inflammatory side-effects are seen with IO including pneumonitis, colitis, and hormone dysfunction. Furthermore, as patients are living longer, the patterns of failure have also altered with more RCC patients presenting with issues of LC from poorly responding and progressive local disease or metastasis [ 33 , 34 , 35 ]. Many patients cannot have surgical resection, due to either technical feasibility or patient factors.…”
Section: Introductionmentioning
confidence: 99%